A blockchain based incentive provisioning scheme for traffic event validation and information storage in VANETs. Issue 2 (March 2021) - Khalid, Adia; Iftikhar, Muhammad Sohaib; Almogren, Ahmad; Khalid, Rabiya; Afzal, Muhammad Khalil; Javaid, Nadeem
Abstract: In Vehicular Ad hoc Networks (VANETs), a large amount of data is shared between vehicles and Road Side Units (RSUs) in real-time. VANETs improve traffic efficiency and reliability by timely sharing road events and traffic information. However, there is a need to tackle the issues of both less data storage capability and selfish behavior of the vehicles. The conventional data storage mechanisms involve a third party for data management and are non-transparent, unreliable, untrustworthy, and insecure. Therefore, a blockchain based data storage system is presented in this paper to overcome the aforementioned issues. The proposed system exploits benefits of an Interplanetary File System (IPFS). Due to the resource constraints of vehicles, the blockchain is implemented on the RSUs. The RSUs get the aggregated packets sent by the vehicles. The packets contain the events' information that occur in the vehicles' surroundings. After verifying a packet, RSUs store the information related to the event in IPFS and reputation value of the sender vehicle in the blockchain. The reputation value of a vehicle is calculated based upon the correctness of an event it signs or initiates. Moreover, an incentive mechanism is also proposed to provide monetary incentives to the replier vehicles who respond to the events' information. The incentives are provided by the initiators after verification of the repliers' signatures. The initiator is a vehicle who initializes the event. The transactions performed during the incentive process are stored in the blockchain. Finally, Oyente tool is used to analyze the security of the proposed smart contract. A comparison of the proposed scheme with the logistic regression scheme is also presented. Highlights: A blockchain based data storage system is presented to overcome the volume and delay issues. The proposed system exploits benefits of an Interplanetary File System (IPFS). Due to the resource constraints of vehicles, the blockchain is implemented on the RSUs. An incentive mechanism is proposed to provide monetary incentives to active vehicles. Oyente tool is used to analyze the security of the proposed smart contract.